2017
DOI: 10.1103/physreve.95.063207
|View full text |Cite
|
Sign up to set email alerts
|

Plasma anisotropy around a dust particle placed in an external electric field

Abstract: A self-consistent model of plasma polarization around an isolated micron-sized dust particle under the action of an external electric field is presented. It is shown that the quasineutral condition is fulfilled and the formed volume charge totally screens the dust particle. The ion focusing and wake formation behind the dust particle are demonstrated for different ion mean free paths and the external electric fields. It is obtained that at low values of the external electric field the trapped ions play the mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…The model presented in this paper was thoroughly described in refs. . Therefore, this chapter describes only the most important changes made to enable the calculation of particles of non‐spherical geometry.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The model presented in this paper was thoroughly described in refs. . Therefore, this chapter describes only the most important changes made to enable the calculation of particles of non‐spherical geometry.…”
Section: Modelmentioning
confidence: 99%
“…In refs. , the authors of this paper demonstrated a model in which the distributions of a space charge and potential were calculated in a self‐consistent way for various plasma parameters. All previously published results consider spherical particles.…”
Section: Introductionmentioning
confidence: 99%
“…In previous research papers, the authors of the present article demonstrated the results of calculations of the model, in which the distributions of volume charges and potentials were determined in a self‐consistent way for various plasma parameters. However, the dependencies of these distributions on one of the main parameters, the ion mean free path of the resonant charge exchange process, have not yet been studied.…”
Section: Introductionmentioning
confidence: 82%
“…To date, several fundamental numerical approaches have been developed, with the help of which effects associated with polarized plasma are calculated. These methods are: particle‐in‐cell method (PIC), linear response method (LR), and method of molecular dynamics (MD) . They allow one to calculate with some degree of accuracy potential distribution around charged dust particles, which are influenced by the plasma flow or are under the action of an external field.…”
Section: Introductionmentioning
confidence: 99%
“…In [17][18][19][20], the authors of this article demonstrated the results of calculations of a model in which the distributions of space charges and potentials were determined in a self-consistent manner also around spherical particles. This article presents the dependences of the density distribution and the space charge potential, as well as the dependence of the dipole moment of the "dust particle -ion cloud" system for nonspherical particles: a flattened and elongated ellipsoid.…”
Section: Introductionmentioning
confidence: 90%